The Role of Liquidity Indicators to Assess its Risks and Enhance Capital Adequacy in Banking Activity - Snjawi, Saadallah Abdullah Kareem; Essa, Serwan Kareem (Journal of Economics and Administrative Sciences, 2021)
This purpose of the research is to test liquidity ratios to assess bank liquidity risks represented by liquidity ratios (current assets / current liabilities, current assets / total deposits, current assets / total assets, cash credit / total deposits, liquidity coverage ratio LCR, net stable financing ratio NSFR). This research involves evaluating these risks in banks via these ratios, and reveal the most important means used to solve these risks, including the capital adequacy ratio under the Basel II decisions and for selected period (2017-2019).The research reached the most important conclusion, which is the bank sample did not fall into bank liquidity risks throughout the years of research. Tracking specific ratio with adequacy capital of Basel II decisions of the Bank, it is noticed that it exceeds the minimum capital adequacy ratio in all valid measures, whether in Basel II decisions with 8% or the requirements of the central bank of Iraq with 12%. The research suggests some recommendations; one of the most important one is the need for the bank’s management to recognize the risks of liquidity in advance, in addition to increasing its investments to increase the bank’s profitability. Moreover, the bank needs to plan a clear strategy to maintain capital at the appropriate and required level to face liquidity risks